2020
DOI: 10.1155/2020/1598503
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Dialyzable Leukocyte Extract IMMUNEPOTENT-CRP Induces Selective ROS-Dependent Apoptosis in T-Acute Lymphoblastic Leukemia Cell Lines

Abstract: Immunotherapies strengthen the immune system to fight multiple diseases such as infections, immunodeficiencies, and autoimmune diseases, and recently, they are being used as an adjuvant in cancer treatment. IMMUNEPOTENT-CRP (I-CRP) is an immunotherapy made of bovine dialyzable leukocyte extract (bDLE) that has chemoprotective and immunomodulatory effects in different cellular populations of the immune system and antitumor activity in different cancer cell lines. Our recent results suggest that the antineoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In T-acute lymphoblastic leukaemia (T-ALLL) cells (Molt-4 and CEM), ICRP provokes ROS-dependent apoptosis accompanied by mitochondrial and nuclear alterations. 11 On the other hand, in cell lines from cervical (HeLa and SiHa cells) and lung cancer (A529 cells), ICRP induces non- apoptotic cell death (caspase-independent) that relies on ROS production, involving cell cycle arrest and loss of mitochondrial membrane potential. 9 , 10 , 13 In this work, we demonstrated that ICRP caused caspase- and necrosome-independent regulated cell death that relies on ROS production in MCF-7, MDA-MB-231 and 4T1 cells, suggesting a conserved mechanism of action in solid tumours, and with some shared characteristics in all the cell lines tested to this day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In T-acute lymphoblastic leukaemia (T-ALLL) cells (Molt-4 and CEM), ICRP provokes ROS-dependent apoptosis accompanied by mitochondrial and nuclear alterations. 11 On the other hand, in cell lines from cervical (HeLa and SiHa cells) and lung cancer (A529 cells), ICRP induces non- apoptotic cell death (caspase-independent) that relies on ROS production, involving cell cycle arrest and loss of mitochondrial membrane potential. 9 , 10 , 13 In this work, we demonstrated that ICRP caused caspase- and necrosome-independent regulated cell death that relies on ROS production in MCF-7, MDA-MB-231 and 4T1 cells, suggesting a conserved mechanism of action in solid tumours, and with some shared characteristics in all the cell lines tested to this day.…”
Section: Discussionmentioning
confidence: 99%
“…IMMUNEPOTENT CRP (ICRP), a bovine dialysable leukocyte extract (DLE) obtained from disrupted spleen, is cytotoxic to several cancer cell lines, 8 11 without affecting the viability of non-cancer cells. 11 ICRP induces ICD in the murine melanoma model B16F10, 12 whereas in HeLa and MCF-7 cells, ICRP-mediated cell death involves CRT exposure, ATP and HMGB1 release, which are the principal damage-associated molecular patters (DAMPs) involved in ICD. In addition, ICRP leads to eIF2α phosphorylation (P-eIF2α), which indicates endoplasmic reticulum (ER) stress, an early ICD biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…IMMUNEPOTENT CRP induces cell death in HeLa and MCF-7 cells through cell cycle arrest, loss of mitochondrial membrane potential and ROS generation ICRP induces regulated cell death in HeLa, SiHa, A549 and A427 cells [2,3], while sparing noncancerous cells [6], however its effect on breast cancer derived-MCF-7 cell line, has not been assessed. Thus, to determine the effect of ICRP in MCF-7 cells, we evaluated cell death induced by different doses of ICRP after 24 h of treatment using HeLa cells and healthy-donor derived PBMC as a control.…”
Section: Resultsmentioning
confidence: 99%
“…IMMUNEPOTENT CRP (ICRP), a bovine dialyzable leukocyte extract (DLE) obtained from disintegrated spleen, is cytotoxic to several cancer cell lines, including those from lung cancer [ 2 ] cervical cancer [ 3 ] and breast cancer [ 4 , 5 ], while sparing noncancerous cells [ 6 ]. In murine melanoma, it prevented cell growth and diminished VEGF release [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been described that an effective combinatorial regimen could be reached based on the targeting of different mechanisms of cell death (Correia et al, 2018[ 6 ]). In that sense, the bovine dialyzable leukocyte extract (bDLE), IMMUNEPOTENT CRP (ICRP), is an immunotherapy with cytotoxic potential in several cancer cell lines (Franco-Molina et al, 2006[ 10 ]) including breast cancer cells, without affecting non-cancerous cells (Martínez-Torres et al, 2020[ 22 ]; Lorenzo-Anota et al, 2020[ 19 ]). Furthermore, the combination of ICRP plus chemotherapy modifies the tumor microenvironment, potentiating and prolonging the antitumor effect (Santana-Krimskaya et al, 2020[ 32 ]).…”
Section: Introductionmentioning
confidence: 99%